2022
DOI: 10.1002/ppul.25854
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Echinococcus in children: A descriptive study in a LMIC

Abstract: By submitting this thesis electronically, I declare that the entirety of the work contained therein is my own, original work, that I am the sole author thereof (save to the extent explicitly otherwise stated), that reproduction and publication thereof by Stellenbosch University will not infringe any third party rights and that I have not previously in its entirety or in part submitted it for obtaining any qualification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…They demonstrated that simple small pulmonary echinococcal lesions could be excised using endostaplers. Mfingwana et al [ 18 ] described a pediatric cohort diagnosed with pulmonary CE and treated with a combination of medical and surgical therapy. In endemic areas of hepatic echinococcosis, laparoscopy should be performed for hepatic cysts that are highly suspected to be CE, as a diagnostic and therapeutic tool.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that simple small pulmonary echinococcal lesions could be excised using endostaplers. Mfingwana et al [ 18 ] described a pediatric cohort diagnosed with pulmonary CE and treated with a combination of medical and surgical therapy. In endemic areas of hepatic echinococcosis, laparoscopy should be performed for hepatic cysts that are highly suspected to be CE, as a diagnostic and therapeutic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative chemotherapy with albendazole or mebendazole is recommended to reduce the risk of secondary echinococcosis after the operation. Initiation of this chemotherapy should begin at least 4 days before the surgical procedure and continue for a duration of at least 1–3 months 3 , 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Limited number of studies have reported renal involvement in pediatric cases 1–3 . In the study by Mfingwana 1 and colleagues, only two cases with lung involvement additionally had spleen involvement, while no case of renal involvement was observed. At the same time, In the study by Çay 2 and colleagues, only three cases with lung involvement additionally had renal involvement.…”
Section: Figurementioning
confidence: 99%
“…The renal involvement was especially significant in this case. Limited number of studies have reported renal involvement in pediatric cases 1–3 . In the study by Mfingwana 1 and colleagues, only two cases with lung involvement additionally had spleen involvement, while no case of renal involvement was observed.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation